2021
DOI: 10.1002/jsfa.11202
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic regulation mechanism of fucoidan via intestinal microecology in diseases

Abstract: The intestinal microecology is an extremely complex ecosystem consisting of gut microbiota, intestinal mucosa and the intestinal immune system. The intestinal microecology performs several important functions and is considered to be an essential ‘organ’ because it plays an important role in regulating human metabolism. Fucoidan contains a large amount of fucose and galactose residues, as well as various other neutral and acidic monosaccharides. Fucoidan particularly effects tumors, inflammatory bowel disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 108 publications
0
20
0
Order By: Relevance
“…Therefore, we speculate that intraperitoneal or subcutaneous injection might be the optimal administration mode of fucoidan for hematopoiesis stimulation. Of course, the intestinal microbiota might be a target of fucoidans, in addition to its direct role in cells [ 66 ]. Although we initially tried to explore and verify the mechanisms of DSFF on related pathways through the above experiments, the question of at which molecular weight fucoidan plays a role and other more detailed mechanisms of DSFF need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we speculate that intraperitoneal or subcutaneous injection might be the optimal administration mode of fucoidan for hematopoiesis stimulation. Of course, the intestinal microbiota might be a target of fucoidans, in addition to its direct role in cells [ 66 ]. Although we initially tried to explore and verify the mechanisms of DSFF on related pathways through the above experiments, the question of at which molecular weight fucoidan plays a role and other more detailed mechanisms of DSFF need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they could be directly recognized and transported into the epithelium by endocytosis of IECs [ 69 ]. It is also assumed that they are absorbed as short-chain fatty acids (SCFAs) by the fermentation by-products from fucoidan [ 70 ]. The transported nutrients from fucoidan as energy sources could enhance intestinal barrier integrity and maintain intestinal homeostasis by interacting with various intestinal cells ( Figure 2 ).…”
Section: Functional Effects Of Fucoidansmentioning
confidence: 99%
“…Although the mechanism of nutrient uptake is still unclear, fucoidan can lead to potential effect on host immunological homeostasis and microbiota composition. The ideas of the figure were based on [ 30 , 66 , 67 , 68 , 69 , 70 ].…”
Section: Figurementioning
confidence: 99%
“…Recent studies have shown that dietary fucoidan supplementation could maintain intestinal health by repairing the intestinal mucosa, enhancing mucosal immune function, and regulating intestinal microflora in mice and pigs [ 12 , 13 , 14 ]. In general, fucoidan has protective effects on the intestinal physical, chemical, immune, and microbial barriers [ 15 , 16 ]. Thus, fucoidan has been widely used as a functional feed supplement.…”
Section: Introductionmentioning
confidence: 99%